A SMYD3/ITGB6/TGFβ1 Positive Feedback Loop Promotes the Invasion and Adhesion of Ovarian Cancer Spheroids - Jiang, Yahui; Zhou, Tianyu; Shi, Yiwen; Feng, Weiwei; Lyu, Tianjiao (Frontiers in Oncology, 2021)
Background: Implantation metastasis is the main means of dissemination in ovarian cancer. Our previous studies showed that SET and MYND domain-containing protein 3 (SMYD3) expression was higher in ovarian cancer spheroids than in monolayers. SMYD3 enhancement of spheroid invasion and adhesion is mediated by the downstream effectors ITGB6 and ITGAM. However, the potential mechanisms underlying the SMYD3/integrin-mediated invasion and adhesion of spheroids still need to be explored. Methods: Western blotting was used to examine the expression of SMYD3, ITGB6 and downstream molecules under different treatments. Immunofluorescence was used to detect the expression of F-actin, E-cadherin and N-cadherin. Anti-ITGB6 antibody-based inhibition and dual-luciferase reporter assays were used to confirm the binding between ITGB6 and latent TGFβ1. Transwell invasion, adherence and 3D tumor spheroid invasion assays were employed to test the effects of TGFβ1 on the invasion and adhesion of ovarian cancer spheroids. ELISA was performed to assess the release of latent TGFβ1 from ovarian cancer spheroids. Results: SMYD3 and ITGB6 activated the TGFβ1/Smad3 pathway and then induced the upregulation of Snail, Vimentin and N-cadherin and the downregulation of E-cadherin in 3D-cultured ovarian cancer spheroids. In this process, latent TGFβ1 could bind to ITGB6 and become activated to stimulate the Smad3 pathway. Moreover, SMYD3 and ITGB6 could facilitate the release of latent TGFβ1 from 3D-cultured ovarian cancer spheroids. Interestingly, TGFβ1 could promote the expression of SMYD3 and ITGB6 via feedback. This positive feedback loop could further amplify the biological effect and promote the invasion and adhesion of ovarian cancer spheroids. Conclusion: Our results demonstrated that the SMYD3/ITGB6/TGFβ1-Smad3 positive feedback loop could promote the invasion and adhesion of ovarian cancer spheroids by upregulating the expression of N-cadherin, Snail, and Vimentin and downregulating the expression of E-cadherin. Thus, our study unmasked the mechanism of SMYD3- and ITGB6-induced ovarian cancer metastasis and provides new ideas for targeted ovarian cancer treatment.